Implementation of Information and Communication Technology Media in Project-Based Learning and Its Impact on Learning Outcomes in Electrolyte and Non-Electrolyte Solution Material - Rian Kadarusman (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the influence of information and communication technology media applied in project-based learning on student learning outcomes in the material of electrolyte and non-electrolyte solutions. Methodology: The research method used was a quasi-experimental design with a pretest and posttest design for two groups. Two classes were randomly selected as the experimental and control groups. The experimental group used information and communication technology media in project-based learning, while the control group used a demonstration method. Data were obtained through tests and analyzed to determine the effect of the treatment. Main Findings: The analysis results show that the use of information and communication technology media in project-based learning has a positive impact on student learning outcomes. This is evidenced by the calculated t value being greater than the t table, which is 2.2, which is greater than 1.671. Furthermore, the posttest score for the experimental group was also higher than that of the control group, indicating a significant improvement in learning outcomes. Novelty/Originality of this study: This study offers novelty by integrating information and communication technology media within project-based learning specifically for electrolyte and non-electrolyte solution topics, which are often abstract for students. It advances existing knowledge by demonstrating how technology-enhanced learning projects improve conceptual understanding and learning outcomes, providing a more interactive and student-centered approach compared to conventional instructional methods.